The The Influence of the Implementation of Think-Pair-Share Method and Self Efficacy toward Students' Mathematical Problem Solving Skills at SMPN 21 Pekanbaru - Ahmad, Risnawati (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 1 No 1 (2017): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami ), 2017)
The aims of this research were to examine the influence the implementation of Think-Pair-Share method toward students' mathematical problem solving skills at grade VIII SMPN 21 Pekanbaru. This research was Quasi Experiment research. The population of this research was all of students at grade VIII in SMPN 21 Pekanbaru. The sample of this research was the students at grade VIII.3 as experiment class and VIII.4 as control class. Data collection techniques in this research were the self-efficacy questionnaire and the mathematical problem solving test. The technique of data analyze was t-test and ANOVA. The results of this research were the following: (1) Students' mathematical problem solving skills that was taught by Think-Pair-Share Method higher than students' skills that was taught by conventional learning. (2) Students' mathematical problem solving skills those have high self-efficacy that was taught by Think-Pair-Share Method higher than students' that was taught by conventional learning. (3) Students' mathematical problem solving skills those have low self-efficacy that was taught by Think-Pair-Share Method higher than the students' was taught by conventional learning. (4) There is no interaction between learning method with self-efficacy of students' mathematical problem solving skills. Hence, Think-Pair-Share Method had good influence upon students' mathematical problem solving skills.